PENGARUH REVIEW CELEBRITY ENDORSEMENT DAN MEDIA SOSIAL TERHADAP MINAT BELI PADA PRODUK KECANTIKAN “MS GLOW” BY OWNER IBU MARISA DI KOTA TANGERANG - Sugiarti, Rista; Haryantini (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of celebrity endorsement and Instagram social media on purchasing interest in Ms Glow beauty products in shops in Tangerang City. This research is quantitative research. The sample for this research was 97 respondents. The sampling technique uses Probability Sampling with Random Sampling type. According to Sugiyono (2018:118) "Probability Sampling is a sampling technique that provides the same opportunity or opportunity for each element or member of the population to be selected as a sample. Primary data collection is obtained from distributing questionnaires. Data processing uses SPSS version 24 software. Data feasibility testing uses validity tests, reliability tests and classical assumption tests. Data analysis techniques use simple linear regression tests, multiple linear regression tests, correlation tests, determination tests and hypothesis tests. The results of this research are that celebrity endorsement reviews (X1) have a positive and significant effect on buying interest, this is proven by the results of the partial test (t test) where the results of tcount > ttable are 5.532 > 1.985 with a significance value of 0.000 <0.05. Social media (X2) also has a positive and significant effect on buying interest, this is proven by the results of the partial test (t test) where the results of tcount > ttable are 15.939 > 1.985 with a significance value of 0.000 < 0.05. Then reviewing celebrity endorsements (X1) and social media (X2) simultaneously have a positive and significant influence, this is proven by the results of the simultaneous test (F test) where the results of Fcount > Ftable are 125.892 > 3.145 with a significance value of 0.000 < 0.05 . Based on the coefficient of determination, the variables celebrity endorsement review (X1) and social media (X2) have a simultaneous influence of 72.8%, while the remaining 27.2% (100%-72.8%) is from epsilon (an indicator of variables that are notresearched).